The Contribution of Ibnu Sina Multilevel Intellect and Neuroscience: in Learning Al-Qur’an Hadith in Vocational High Schools in the Covid-19 Era - Mohammad Jailani; Suyadi Suyadi (DAYAH: Journal of Islamic Education, 2023)
Due to the Covid-19 pandemic, learning of the Qur'an and Hadith is less effective, its impact on student learning. One of them is because learning is not by the brain-based way of learning for students. This study aims to analyze the learning of Al-Qur'an Hadith at SMK Muhammadiyah 3 Yogyakarta in the covid-19 era from the perspective of Ibn Sina's multilevel reasoning and neuroscience. This research data through (search) the literature description of scientific journals and observation of research work references, as well as interview information data at schools. This research is a literature study with a qualitative method. Research results prove that learning the Qur'an and Hadith based on Ibn Sina's level of reasoning and neuroscience, can understand the material theoretically and empirically, both theoretically learning with tajwid and in practice the law of recitation and makhurijul huruf. Learning that has implications for students in understanding, developing interest, evaluating, and producing learning works on the discourse of the Qur'an Hadith.